Pengaruh Pelaksanaan Keselamatan dan Kesehatan Kerja (K3) dan Lingkungan Kerja pada Kepuasan Kerja Karyawan pada PT Karimun Sembawang Shipyard - Vira Putri Farisha; Suryalena Suryalena (eCo-Buss, 2023)
The purpose of this study is to identify and analyze the impact of occupational health and safety (K3) and working environment on job satisfaction of employees at PT Karimun Sembawang shipyard. In this study, occupational health and safety and working environment were used as independent variables, and job satisfaction as dependent variables. The methods used in this study are descriptive statistics and quantitative analysis. The sample for this study included 70 respondents or the entire population using census methods. Data were obtained from the results of completed questionnaires and analyzed using SPSS. The results show that PT Karimun Sembawang Shipyard's K3 is in the good category, the working environment is in the good category, and the job satisfaction is in the good category. The results of the hypothesis test show that occupational safety and health protection has a significant positive impact on job satisfaction. Work environment has a positive and significant impact on job satisfaction. Meanwhile, occupational safety and working environment affect job satisfaction of PT Karimun Sembawang Shipyard employees.